2016
DOI: 10.1007/s00705-016-2972-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of feline bocavirus detected in cats in Japan

Abstract: Feline bocavirus (FBoV) has been classified into three genotypes (FBoV1-FBoV3). FBoVs are mainly detected in feces. In the present study, we collected rectal swabs from cats in Japan and examined the samples for the presence of FBoV. The FBoV infection rate was 9.9 % in 101 cats. No significant association was observed between FBoV infection and clinical symptoms. Based on the full-length NS1 protein, the three strains of FBoVs detected in the present study shared high homologies with the genotype 2 FBoV POR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
0
30
1
Order By: Relevance
“…It has been demonstrated that not only FPV can infect cats but also that the different subtypes of CPV-2 (CPV-2a, CPV-2b and CPV-2c) can infect domestic cats, causing diarrhea [2]. In addition, in previous studies, FBoV has been classified into three genotypes (FBoV-1, FBoV-2 and FBoV-3) [22] and FeAstV has been classified into different genotypes [24]. In the present study, we designed three pairs of universal primers that can detect the different genotypes of the three viruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that not only FPV can infect cats but also that the different subtypes of CPV-2 (CPV-2a, CPV-2b and CPV-2c) can infect domestic cats, causing diarrhea [2]. In addition, in previous studies, FBoV has been classified into three genotypes (FBoV-1, FBoV-2 and FBoV-3) [22] and FeAstV has been classified into different genotypes [24]. In the present study, we designed three pairs of universal primers that can detect the different genotypes of the three viruses.…”
Section: Discussionmentioning
confidence: 99%
“…FeAstV was first reported in 1981 in faeces from diarrheic cats [9], and a novel FeAstV genotype was found in 2012 [11]; however, studies on FeAstV pathogenicity are limited. FBoV was first detected in a stray cat in Hong Kong in 2012 [10] and has been reported in the USA [27], Portugal [17], Japan [22] and China [25]. According to the latest report of the International Committee on Taxonomy of Viruses (ICTV), FBoV-1, FBoV-2 and FBoV-3 have been recognized as members of the species Carnivore bocaparvovirus 3, 4, and 5, respectively, within the genus Bocaparvovirus [5], based on the amino acid sequence of the complete NS1 gene [25].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The detection of kobuvirus was performed by RT-PCR using a pair of universal primer previously described (the primer sequences are shown in Table 1), UNIV-kobu-F/UNIV-kobu-R targeting 217-bp of partial 3D gene for all kobuviruses (Reuter et al 2009). These samples were also examined for other feline enteric viruses, including feline parvovirus (FPV) and feline bocavirus (FBoV), using PCR assays previously described (Takano et al 2016;Yang et al 2010). The amplified products were separated after electrophoresis on 1.5% agarose gels at 160 V for…”
Section: Detection Of Fekov and Other Feline Enteric Virusesmentioning
confidence: 99%
“…Previous research has demonstrated that genetically diverse bocaviruses are present in cats, dogs and minks worldwide [6,11,21,23,24]. To date, six members of the genus Bocaparvovirus have been identified in carnivores.…”
mentioning
confidence: 99%